Legal Protection For Victims of Cyberspace Doxing in The Digital Age - Zakiah (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2025)
This research aims to analyze the legal protection for victims of doxing in Indonesia from victimology and restorative justice principles. This study employed a normative legal method approach. The findings reveal that although Indonesia has several relevant legal instruments, there is no specific provision explicitly addressing doxing as a criminal offense. This regulatory gap has led to challenges in the implementation of victim protection. Law enforcement efforts still face obstacles, such as the limited understanding of digital crime among law enforcement officers, low digital literacy within society, and inadequate psychosocial. recovery services for victims. Therefore, synergy is needed through regulatory reform, institutional capacity building, active community participation, and the strengthening of psychosocial rehabilitation services for victims. These findings highlight the importance of integrating legal approaches with a victimology perspective to ensure comprehensive and fair legal protection for victims of doxing.